2020
DOI: 10.1186/s40792-020-01047-w
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair using a covered stent for a ruptured infected aneurysm of the superior mesenteric artery after pancreaticoduodenectomy: a case report

Abstract: Background Delayed arterial hemorrhage after pancreaticoduodenectomy is a life-threatening complication. There are no reports about infected aneurysms of the superior mesenteric artery after pancreaticoduodenectomy without clinically relevant pancreatic fistula. Case presentation A 78-year-old woman with borderline resectable pancreatic ductal adenocarcinoma involving the superior mesenteric arterial nerve plexus underwent pancreaticoduodenectomy with en bloc resection of the superior mesenteric vein and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In another case, even though a troublesome focus of brain abscess was diagnosed, the patient had an indolent clinical course and successfully recovered without any complications [ 7 ]. Uncommon complications include hemorrhagic shock (due to GIT bleeding), peritonitis, multi-organ failure, biloma, empyema, and intra-abdominal sepsis [ 24 , 31 , 37 , 57 , 69 , 80 ]. Thrombosis can persist, resolve (entirely or partially), or result in a cavernous transformation of the portal vein (i.e., the formation of veins within or around the previously thrombosed PV) [ 64 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another case, even though a troublesome focus of brain abscess was diagnosed, the patient had an indolent clinical course and successfully recovered without any complications [ 7 ]. Uncommon complications include hemorrhagic shock (due to GIT bleeding), peritonitis, multi-organ failure, biloma, empyema, and intra-abdominal sepsis [ 24 , 31 , 37 , 57 , 69 , 80 ]. Thrombosis can persist, resolve (entirely or partially), or result in a cavernous transformation of the portal vein (i.e., the formation of veins within or around the previously thrombosed PV) [ 64 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease is significant and might imply that the identification and treatment of pylephlebitis have improved over time. Sepsis was the cause of death in 88.9% of patients who died, with one patient (11.1%) dying due to pancreatic adenocarcinoma [ 37 ]. Our review found that the independent risk factors for mortality in patients suffering from pylephlebitis are positive blood cultures, pertinent comorbidities, and sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PSAs are associated with a high mortality rate [ 23 ]. In this scenario, prompt intervention is a cornerstone.…”
Section: Discussionmentioning
confidence: 99%
“…This significant decrease in mortality might suggest that the identification and treatment of pylephlebitis have improved over time. Sepsis has been found to be the cause of death in approximately 88.9% of patients [221], increasing the risk of death 17-fold [208]. Positive blood cultures were also found to be an independent risk factor for death (approximately 2.2-fold) [208].…”
Section: Complications and Mortalitymentioning
confidence: 98%